EDUCATION POLICY IN INDIA: TRENDS, CHALLENGES, AND FUTURE DIRECTIONS - Dr. Pravin R. Choube (Western European Studies, 2025)
Education policy in India has undergone significant transformations over the past decade, reflecting efforts to achieve universal access, improve quality, and integrate modern technology and skill development. This paper examines the evolution of Indian education policy, focusing on recent initiatives such as the National Education Policy (NEP) 2020, state-level reforms, and government-led digital education programs. Using a combination of policy analysis, statistical data, and case studies, the study highlights key achievements, persistent challenges, and opportunities for future improvement. The findings emphasize the importance of equitable access, curriculum innovation, teacher development, and digital infrastructure in realizing educational goals
Keywords: Education policy; India; NEP 2020; curriculum reform